What Drives Responses to Willingness-to-pay Questions? A Methodological Inquiry in the Context of Hypertension Self-management - Billingsley Kaambwa; Stirling Bryan; Emma Frew; Emma Bray; Sheila Greenfield; Richard J McManus (Journal of Health Economics and Outcomes Research)
**Background:** The use of economic evaluation to determine the cost-effectiveness of health interventions is recommended by decision-making bodies internationally. Understanding factors that explain variations in costs and benefits is important for policy makers.